KOMPARASI STRUKTUR KURIKULUM INDONESIA DAN FINLANDIA: STUDI LITERATUR TERHADAP IMPLEMENTASI PEMBELAJARAN ABAD KE-21 - Juwita, Riris Mawar; Rosmalina Dwihastuti; Uun Bahriana; Yohana Widya Elisa Putri; Verawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Curriculum plays an important role in determining the direction and quality of education in a country. The development of globalization and technology requires educational systems to produce students who possess 21st-century competencies such as critical thinking, creativity, communication, and collaboration. This study aims to compare the educational curriculum structures of Indonesia and Finland through a literature study method. The research data were obtained from scientific journals, books, academic articles, and educational policy documents published between 2020 and 2025. The findings indicate that Finland’s curriculum is more flexible, student-centered, and emphasizes student well-being as well as holistic competency development. Meanwhile, Indonesia has transformed its curriculum toward competency-based learning through the Merdeka Curriculum, although challenges remain in implementation, educational equality, and assessment systems. The main factors contributing to the success of Finland’s curriculum include teacher quality, pedagogical autonomy, positive learning culture, and consistency of educational policies. Therefore, Indonesia needs to strengthen teacher competency development, simplify learning materials, and reinforce process-based assessment systems.